If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x * x + 4x + 30 = 0 Multiply x * x -2x2 + 4x + 30 = 0 Reorder the terms: 30 + 4x + -2x2 = 0 Solving 30 + 4x + -2x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '2'. 2(15 + 2x + -1x2) = 0 Factor a trinomial. 2((5 + -1x)(3 + x)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(5 + -1x)' equal to zero and attempt to solve: Simplifying 5 + -1x = 0 Solving 5 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -1x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -1x = 0 + -5 -1x = 0 + -5 Combine like terms: 0 + -5 = -5 -1x = -5 Divide each side by '-1'. x = 5 Simplifying x = 5Subproblem 2
Set the factor '(3 + x)' equal to zero and attempt to solve: Simplifying 3 + x = 0 Solving 3 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + x = 0 + -3 x = 0 + -3 Combine like terms: 0 + -3 = -3 x = -3 Simplifying x = -3Solution
x = {5, -3}
| 10.24=y/4 | | 5(x-3)+2(x+2)=50 | | 3e^3+72e=33e^2 | | 36=5y+4y | | j^2-2=17 | | i^2+6=6 | | 180=21+x-1 | | g(x)=x-14 | | 2y=10x-7 | | 10t-28=12t-52 | | 180=42+8+x | | 3w+7+9w= | | 27+7c=150+c | | 13h^2-3=4209 | | 7s+4s=-72 | | -3x*x-75=0 | | 7+6n=37 | | 42-2r=165-3r | | 2a=a+44 | | 12-5u=-15 | | 6(v-4)-8v=-20 | | 2y+6(y+2)=-36 | | x=5-1/x | | 0.2x-0.4(5-x)=0.7 | | x*x-23=52-2*x*x | | 5m-4=41 | | 1/x=5-x | | 8(w-4)-5w=-17 | | 18-2x=(x-9) | | 2x+4+8x-8=180 | | ln(13/x) | | -10(s+3)=-21 |